La discriminación social luego del cumplimiento de la pena privativa de libertad. - Quivintuña Quivintuña, Wilmer Efraín (2023)
The present work has the purpose of making known the existence of discrimination produced against people who have served their custodial sentence, since this directly affects people who reintegrate into society after having served their sentence. conviction, adequate public policies have not been developed that allow a true social reintegration so that in this way there is no type of discrimination, reintegration into society is a process that involves all actions aimed at improving the conditions and opportunities for the people who were deprived of their liberty, which facilitates their access to work, education, health and other opportunities, this with the purpose of reducing the risk of criminal recidivism. Society plays an important role in ensuring that people who have been deprived of their liberty for different reasons; They can reintegrate into society and especially in the workplace and thus they can obtain economic resources in an honest way without the need to commit criminal acts to satisfy their personal needs and those of their family, but the ex-convicts become discriminated against for having a criminal record. Despite the fact that the Constitution of the Republic has determined in article 11 that no person should be discriminated against due to their judicial past, this provision is not respected. The methodology with which the research project is carried out was through the application of the quantitative, legal, bibliographic method; descriptive, inductive and deductive were used as the type of research; and the research technique was the interview with the chosen population that belongs to the Canton of Guaranda of the Province of Bolívar, in this way I can obtain the conclusions and recommendations regarding social discrimination against the ex-sentenced. Keywords: Discrimination, Equality, Judicial Past, Rehabilitation, Social Reintegration.